The secret war : spies, codes and guerrillas 1939-45 - Hastings, Max, 1945- 1945- (William Collins, 2015)
Examining the espionage and intelligence stories of World War II, on a global basis, bringing together the British, American, German, Russian and Japanese histories. In "The Secret War", Max Hastings examines the espionage and intelligence machines of all sides in World War II, and the impact of spies, code-breakers and partisan operations on events. Written on a global scale, the book brings together accounts from British, American, German, Russian and Japanese sources to tell the story of a secret war waged unceasingly by men and women often far from the battlefields but whose actions profoundly influenced the outcome